Medial tibial stress fracture diagnosis and treatment guidelines. Issue 6 (June 2021) - Milgrom, Charles; Zloczower, Elchanan; Fleischmann, Chen; Spitzer, Elad; Landau, Regev; Bader, Tarif; Finestone, Aharon S.
Abstract: Objectives: To validate and make evidence based changes to the Israel Defense Forces medial tibial stress fracture diagnosis and treatment protocol. Design: Prospective cohort study. Methods: 429 Elite infantry recruits were reviewed for signs and symptoms of medial tibial stress fracture during 14 weeks of basic training. Suspicion of medial tibial stress fracture was based on the presence of pain, tenderness <1/3 the length of the tibia and a positive fulcrum and/or hop test. Recruits with suspected medial tibial stress fractures were initially treated with 10–14 days of rest. Bone scan was performed only when recruits failed to respond to the rest regimen or required immediate diagnosis. Results: 31 Out of 49 recruits with a suspicion of medial tibial stress fracture underwent bone scan, including 8/26 recruits whose symptoms did not resolve after being treated clinically as stress fractures. There was a significantly greater incidence of medial tibial stress fractures when a positive hop test was present in addition to tibial pain and tenderness (p = 0.0001), odds ratio 52.04 (95% CL, 2.80–967.74). Medial tibial stress fracture was found to occur when the band of tibial tenderness was ≤10 cm in length. Tibial pain scores were not predictive of stress fracture. Conclusions: This validation study provides the clinician with evidence based guidelines for the clinical diagnosis and treatment of medial stress fractures and their differentiation from shin splints. An initial treatment protocol without the use of imaging was found to be effective in more than two-thirds of the cases.